The Yığma Tepe of Pergamon: stratigraphic construction of a monumental tumulus from seismic refraction measurements. Issue 2 (20th January 2020) - Mecking, Rebekka; Meinecke, Matthias; Erkul, Ercan; Driehaus, Birte; Bolten, Andreas; Pirson, Felix; Rabbel, Wolfgang
Abstract: The monumental tumulus Yığma Tepe is an important part of the cityscape of the ancient city of Pergamon. The tumulus construction is estimated in the Hellenistic period, the internal structure and exact purpose have been unknown so far. Its height of 32 m and diameter of 158 m make the deep interior of the tumulus practically inaccessible for excavations. Therefore, we applied a combination of geophysical measurements and archaeological sondages to explore the structure of the Yığma Tepe. The investigations centre on P‐wave refraction soundings. They were carried out to clarify the stratigraphic structure and soil composition as a prerequisite for a better understanding of construction techniques, building history and soil deposition. Interactive seismic raytracing, traveltime tomography and visco‐elastic forward modelling were applied to derive a three‐dimensional seismic velocity model, which was validated by excavations and soil analysis, historical records and additional geoelectric measurements. Our results reveal that the tumulus is composed of three layers, each about 10 m thick, separated by first‐order seismic discontinuities which were locally verified. These layers form a stack of conical disks, the interfaces of which define two internal plateaus. The analysis of soil samples showed that the seismic velocity increase at the interfaces is likely to be caused by anthropogenic compaction applied to soils showing increased fractions of silt and clay. By combining topographic data with results from seismic and geoelectric sounding on the tumulus, the surrounding trench and the unaltered surrounding area, we show that the tumulus was built almost completely from the surrounding soils and that 17% of its original volume was displaced by destruction and erosion. Based on this mass balance the strongly destroyed and eroded original surface of the tumulus and its surrounding trench is reconstructed.